2010
DOI: 10.1016/j.bpj.2010.07.057
|View full text |Cite
|
Sign up to set email alerts
|

Probing Field-Induced Tissue Polarization Using Transillumination Fluorescent Imaging

Abstract: Despite major successes of biophysical theories in predicting the effects of electrical shocks within the heart, recent optical mapping studies have revealed two major discrepancies between theory and experiment: 1), the presence of negative bulk polarization recorded during strong shocks; and 2), the unexpectedly small surface polarization under shock electrodes. There is little consensus as to whether these differences result from deficiencies of experimental techniques, artifacts of tissue damage, or defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…This is consistent with previous optical measurements of shock-induced polarizations on the cut transmural surface in left ventricular wedge preparations [1] and measurements obtained noninvasively in isolated right ventricular preparations [10]. Such Δ V m could represent secondary sources of polarization formed by microscopic discontinuities in the tissue structure.…”
Section: Optrode Performancesupporting
confidence: 91%
“…This is consistent with previous optical measurements of shock-induced polarizations on the cut transmural surface in left ventricular wedge preparations [1] and measurements obtained noninvasively in isolated right ventricular preparations [10]. Such Δ V m could represent secondary sources of polarization formed by microscopic discontinuities in the tissue structure.…”
Section: Optrode Performancesupporting
confidence: 91%
“…24, 25 However, other experiments at near-threshold field strengths reported the lack of activation on the myocardial surface under the cathode, which suggested that surface polarization was indeed very small and could not be explained by existing models. 11, 26 Nevertheless, these findings failed to attract attention to this significant inconsistency. A major criticism of previous experimental reports questioning the validity of the existing models 27 was that the observations were likely experimental artifacts caused by tissue damage.…”
Section: Discussionmentioning
confidence: 97%
“…The preparations were perfused through respective coronary arteries, mounted between mesh field electrodes, and stained with the near-infrared dye DI-4-ANBDQBS (40 μM) as described previously. 11 Figure 1a shows a schematic of the experimental setup. A pulsed electric field was applied transmurally from planar mesh electrodes, sufficiently sparse for passage of both illumination light and voltage-sensitive fluorescence signals.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, recorded signals at larger depths can become distorted, as fluorescence imaging is depth integrated for two-dimensional imaging techniques such as optical mapping, making it hard to understand the threedimensional (3-D) wave propagation in whole hearts. Larger penetration depths and improved signal qualities have been demonstrated in whole hearts 30,[32][33][34] and heart slices 27,[37][38][39][40] using near-infrared voltage-sensitive dyes; however, imaging depth still remains limited. Thus, optical recordings of important features of the conduction system, such as the PS lying close to the endocardial surface, 41 have remained unexplored in the intact heart due to the inadequacies of current imaging methods.…”
Section: Optical Mappingmentioning
confidence: 99%
“…High-resolution CCD cameras and EMCCD cameras have been popular for use in optical mapping [5][6][7][30][31][32][33][34][37][38][39][40]127,128,144 and microendoscopy due to their high-spatiotemporal resolution. EMCCD cameras take advantage of avalanche processes to perform the on-chip electron multiplication to enhance SNRs, have higher frame rates, and improved quantum efficiency.…”
Section: Detectorsmentioning
confidence: 99%